A probably invasive new genus and new species of soft coral (Octocorallia: Alcyonacea: Clavulariidae) from Brazil - van Ofwegen, L. P.; Haddad, M. A. (Zootaxa, 2011)
Stragulum bicolor n. gen. & n. sp. (Octocorallia: Clavulariidae) is described from Brazil. It was found in shallow waters of the States of Ceará, Rio de Janeiro, São Paulo, Paraná and Santa Catarina, and is probably invasive. The genus forms encrusting sheets on solid objects, such as seaweed basal stems, barnacle shells and artificial substrates. The new taxon has spindles, crosses and radiates in the outer layer of the coenenchyme, fused sclerites in the interior and the polyps are unarmed. The new genus is compared with other taxa that have fused sclerites.